Identification and Characteristics of Fusion Peptides Derived From Enveloped Viruses - Lozada, Camille; Barlow, Thomas M. A.; Gonzalez, Simon; Lubin-Germain, Nadège; Ballet, Steven (Frontiers in Chemistry, 2021)
Membrane fusion events allow enveloped viruses to enter and infect cells. The study of these processes has led to the identification of a number of proteins that mediate this process. These proteins are classified according to their structure, which vary according to the viral genealogy. To date, three classes of fusion proteins have been defined, but current evidence points to the existence of additional classes. Despite their structural differences, viral fusion processes follow a common mechanism through which they exert their actions. Additional studies of the viral fusion proteins have demonstrated the key role of specific proteinogenic subsequences within these proteins, termed fusion peptides. Such peptides are able to interact and insert into membranes for which they hold interest from a pharmacological or therapeutic viewpoint. Here, the different characteristics of fusion peptides derived from viral fusion proteins are described. These criteria are useful to identify new fusion peptides. Moreover, this review describes the requirements of synthetic fusion peptides derived from fusion proteins to induce fusion by themselves. Several sequences of the viral glycoproteins E1 and E2 of HCV were, for example, identified to be able to induce fusion, which are reviewed here.